Interobserver variation of clinical oncologists compared to therapeutic radiographers (RTT) prostate contours on T2 weighted MRI. (March 2023) - Adair Smith, Gillian; Dunlop, Alex; Alexander, Sophie E.; Barnes, Helen; Casey, Francis; Chick, Joan; Gunapala, Ranga; Herbert, Trina; Lawes, Rebekah; Mason, Sarah A.; Mitchell, Adam; Mohajer, Jonathan; et al.
Highlights: The majority of radiographers prostate and seminal vesicle contours are within a range of clinicians' contours. DSC of radiographer prostate and seminal vesicle contours are comparable to clinicians. There was no significant difference in the HD or MDA between the clinicians and radiographers when compared to a gold standard. Abstract: The implementation of MRI-guided online adaptive radiotherapy has enabled extension of therapeutic radiographers' roles to include contouring. An offline interobserver variability study compared five radiographers' and five clinicians' contours on 10 MRIs acquired on a MR-Linac from 10 patients. All contours were compared to a "gold standard" created from an average of clinicians' contours. The median (range) DSC of radiographers' and clinicians' contours compared to the "gold standard" was 0.91 (0.86–0.96), and 0.93 (0.88–0.97) respectively illustrating non-inferiority of the radiographers' contours to the clinicians. There was no significant difference in HD, MDA or volume size between the groups.